Private Metropolis : The Eclipse of Local Democratic Governance - Alexander, Alba; McKenzie, Evan; Judd, Dennis R. (Book collections on Project MUSE., 2021)
"Examines the complex ecology of quasi-public and privatized institutions that mobilize and administer many of the political, administrative, and fiscal resources of today's metropolitan regions"--